Anestesia com óleo essencial de Lippia alba seguida de atordoamento elétrico ou hipotermia: impacto sobre indicadores de estresse e qualidade da carne de Jundiá (Rhamdia quelen) - Veit, Juliana Cristina (2016)
This study aimed to optimize the electrical stunning for silver catfish and to evaluate whether the anesthesia with essential oil (EO) of L. alba before electrical stunning or hypothermia, used in pre-slaughter stunning stage, would reduce stress and influence on stability and sensory characteristics of fish produtcts. The effect of electrical frequencies between 50 and 1000 Hz associated to 128 or 256 V m-1 electric field strength and duration of exposure to the current between 1 and 60 seconds were evaluated. The electrical frequencies of 100, 300 and 500 Hz, combined with electric field strength of 128 V m-1 during 5 seconds were the most appropriate electrical combinations for pre-slaughter stunning of silver catfish as they yielded longer apparent stunning, lower levels of glucose and lactate and smaller changes in flesh characteristics compared to the others. Anesthesia with EO (300 mg L-1) did not reduce the biochemical markers of stress in silver catfish. However, compared to non-anesthetized fish, anesthesia did delay the loss of freshness and deterioration of chilled fish as it delayed the degradation of ADP to AMP and the generation of inosine, and contributed to reduce the sensory demerit scores for overall and gills odor, belly firmness and whole TFRU scheme, especially when associated with the electrical stunning. Furthermore, non-anesthetized fish were unacceptable for consumption on the 23rd day of chilled storage, whereas anesthetized fish become unacceptable only on the 33rd day. The EO also showed antimicrobial activity against Enterobacteriaceae species, however, when used before hypothermia the EO anesthesia did not prevent the post mortem oxidative changes in the frozen fillets, and potentialized lipid oxidation of frozen fillets when associated with electrical stunning. Hypothermia stunning did modify post mortem changes of fish stored in ice, however fillet from fish submitted to hypothermia had greater oxidation of sulfhydryl groups and protein carbonylation with consequent reduction in lightness and increase in yellowness along frozen storage, which may be responsible for the greater total color difference and increased elasticity of fillets over 18 months of frozen storage compared to electrical stunning. In contrast, electrical stunning resulted in faster onset of rigor mortis than hypothermia but did not accelerate the resolution of rigor mortis or the degradation of ATP in whole fish stored in ice. In addition, electrical stunning favored the generation of hydroperoxides in fillets by the end of frozen storage, as well as more intense red color at the beginning of storage. Thus, electrical stunning with 128 V m-1 electric field strength combined with 300 Hz frequency during 5 seconds, can be used in the pre-slaughter stunning of silver catfish as it was less stressful for fish than hypothermia and did not have any negative effect on the post mortem stability of chilled fish or frozen fillets compared to hypothermia. In addition, prior anesthesia with 300 mg L-1 of EO of L. alba may also be used in this step of the fish processing, especially for whole fish stored in ice.